The moderating effects of exchange rates and interest rates between economic indicators and the level of RMB internationalisation - Meng, Xiang Fu (2024)
The internationalization of the RMB will bring benefits to the country's international economy and trade, such as reducing transaction cost and risks as well as improving trade efficiency and benefits. However, the current level of RMB internationalization is low, and it has become particularly important to study what factors limit the improvement of the level of RMB internationalization. The Chinese government has achieved some achievements since promoting the internationalization of the RMB. However, there is still a big gap between the level of RMB internationalization and the international currency level of developed countries. Moreover, the increasingly-complex international political environment and fierce international market competition have put forward higher requirements for the level of RMB internationalization. Therefore, it is very important to study the influencing factors of the level of RMB internationalization and the impact of national macroeconomic control tools on the level of RMB internationalization to further improve the level of RMB internationalization. International monetary theory is an important theoretical basis for currency internationalization. It is a comprehensive and systematic theoretical basis for studying the influencing factors of RMB internationalization. This study examined the effect of the balance of payments, money supply, and foreign exchange reserves on the level of RMB internationalization, and the moderating effects of exchange rates and interest rates on the relationship between the balance of payments, money supply, foreign exchange reserves and the level of RMB internationalization. Therefore, the philosophical basis of this study is positivism, the hypothetical-deductive research method was adopted, quantitative analysis was used to verify the relationship between the hypothetical variables, and based on the international monetary theory, the quarterly data of 2010-2022 was selected as a sample, and regression analysis model was constructed empirically using the software EVIEWS. The international balance of payments, money supply, and foreign exchange reserves were selected as independent variables, exchange rate and interest rate were introduced as adjusting variables, and the level of RMB internationalization was used as the dependent variable. The study found that the international balance of payments, money supply and foreign exchange reserves would have an effect on the level of RMB internationalization, but the degree of effect was different. Exchange rates and interest rates had a significant regulating effect on the relationship between the balance of payments, money supply, foreign exchange reserves, and the level of RMB internationalization. Among them, the exchange rate had a promoting or inhibiting moderating effect on different variables, but the interest rate had a negative moderating effect on the internationalization of the RMB. Based on the research conclusions, policy recommendations are put forward for the internationalization of the RMB. The RMB should further expand the financial market and formulate a reasonable exchange rate floating policy; and in order to improve the level of RMB internationalization, appropriate low interest rates should be maintained. The significance of this study lies in the fact that it is the first time that the international monetary theory is applied to the study of the influencing factors of the RMB's internationalization level, and the influencing factors of the RMB's internationalization level is systematically and comprehensively analyzed, which fills the theoretical gaps in the study of the influencing factors of the RMB's internationalization level; and, second, it quantitatively analyzes, using the data, the extent to which the exchange rate and interest rate have an impact on the internationalization level of the RMB, and the moderating effect of the exchange rate and interest rate on the different influences on the RMB's internationalization, which provides an important reference for the Chinese government's policy making. The novelty of this study is that it empirically analyzes the moderating effects of exchange rates and theories, and for the first time, applies international monetary theories to the study of RMB internationalization. In addition, the limitation of this study is that only economic factors are considered while contingencies are not taken into account.